COUNSELING ON "THE IMPORTANCE OF STORYTELLING TO THE CLOSEST PEOPLE FOR THE ELDERLY" IN BANDARHARJO VILLAGE, NORTH SEMARANG DISTRICT, SEMARANG CITY - Wihda Almubarok; Wening Wihartati (Jurnal Abdisci, 2024)
This research aims to explore the importance of telling stories to the people closest to the elderly in Bandarharjo Village, North Semarang District. Using a qualitative approach which includes in-depth interviews and observations, this research focuses on elderly people aged 60-82 years who are active in Posyandu Lansia. Data was collected to explore older adults' experiences of sharing stories and the impact on their emotional well-being. The research results show that sharing stories not only helps elderly people express feelings and reminisce about memories, but also serves as a means of reducing feelings of loneliness and increasing a sense of connectedness with those closest to them. This research emphasizes the importance of social support and good communication in improving the quality of life of older people, and provides insight into how simple activities such as telling stories can contribute to their mental and emotional health.